Determinan Efisiensi Perbankan Syariah di Indonesia (Pendekatan Error Correction Model) - Fathurrahman, Ayif; Wulandari, Agustina Ayu (JES (Jurnal Ekonomi Syariah), 2025)
This study aims to analyze the factors that affect the level of efficiency in Islamic Banks. The sample data used are all Islamic Commercial Banks in Indonesia from 2013 to 2019 with a total of 84 objects of observation. The dependent variables used in this study are Operational Costs to Operational Income (BOPO) and independent variables, namely Third-Party Funds (DPK), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Short Term Mismatch (STM), Inflation, and the BI Rate which is obtained from the monthly data reports for Islamic Commercial Banks published by the Financial Services Authority (OJK). The analysis method used is the Error Correction Model (ECM). Based on the results of the ECM analysis, it was found that in the short term DPK, CAR, and FDR had a negative and significant effect on BOPO. STM and inflation variables have a negative and insignificant effect on BOPO and the BI Rate variable has a positive and insignificant effect on BOPO. Meanwhile, in the long term DPK, CAR, FDR, STM, and BI Rate have a negative and significant effect on BOPO. Then for inflation has a positive and significant effect on BOPO.